2014
DOI: 10.1016/j.cmpb.2014.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Automated estimation of disease recurrence in head and neck cancer using routine healthcare data

Abstract: We have demonstrated that our algorithm can be used to automate the interpretation of routine datasets to extract survival information for this sample of patients. It currently underestimates recurrence rates due to many patients not being well-enough to be treated for recurrent disease. With some further optimisation, this technique could be extended to a national level, providing a new approach to measuring outcomes on a larger scale than is currently possible. This could have implications for healthcare pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 11 publications
0
15
1
Order By: Relevance
“…Ricketts et al developed an automated method to estimate the recurrence of head and neck cancers using a sample from a cancer center in the United Kingdom . In their cohort, there were 122 patients with head and neck cancer of whom 51 had oropharyngeal cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ricketts et al developed an automated method to estimate the recurrence of head and neck cancers using a sample from a cancer center in the United Kingdom . In their cohort, there were 122 patients with head and neck cancer of whom 51 had oropharyngeal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…One study explored the use of treatment data from one cancer center in the United Kingdom to identify recurrences of head and neck cancers and reported that their algorithm had moderate validity; however, the sample size of this previous study was small and not population based. More importantly, the algorithm was not applicable to Canada because of the differences in data availability and data systems.…”
Section: Introductionmentioning
confidence: 99%
“…This is less relevant to a study focusing on perioperative outcomes of major surgery than it would be a long‐term oncological study, but as previously discussed, HES data can be linked to other data silos. Administrative data can also provide information about recurrence and disease‐free survival . As such, it has the capacity to provide the infrastructure for a disease‐specific responsive quality control framework for perioperative and oncological quality control, that once activated, could perpetually provide information about care quality and outcome at a frequency that is not achievable using other data submission exercises.…”
Section: Discussionmentioning
confidence: 99%
“…To select only patients with recurrent disease, only those individuals who initiated PPT 120 days or more after discontinuing platinum-based therapy were selected. 15 A live meeting of US-based oncologists (who had treated !5 SCCHN patients in the last 12 months) was convened to evaluate the validity of this previously published algorithm. 16 Those patients with progression prior to 120 days (i.e.…”
Section: Methodsmentioning
confidence: 99%